RANKL-Targeted Therapies: The Next Frontier in the Treatment of Male Osteoporosis - Alicia K. Morgans; Matthew R. Smith (Journal of Osteoporosis)
Male osteoporosis is an increasingly recognized problem in aging men. A common cause of male osteoporosis is hypogonadism. Thousands of men with prostate cancer are treated with androgen deprivation therapy, a treatment that dramatically reduces serum testosterone and causes severe hypogonadism. Men treated with androgen deprivation therapy experience a decline in bone mineral density and have an increased rate of fracture. This paper describes prostate cancer survivors as a model of hypogonadal osteoporosis and discusses the use of RANKL-targeted therapies in osteoporosis. Denosumab, the only RANKL-targeted therapy currently available, increases bone mineral density and decreases fracture rate in men with prostate cancer. Denosumab is also associated with delayed time to first skeletal-related event and an increase in bone metastasis-free survival in these men. It is reasonable to investigate the use of RANKL-targeted therapy in male osteoporosis in the general population.